The DBS Handbook Of Geology - Devi, Renu (New Delhi: Dbs Imprints, 2021)
The DBS Handbook of Geology chronicles the origins and evolution of geology as a crucial scientific discipline in a highly detailed and interesting format. The events that prompted it study, its development throughout the ages, the debates and issues surrounding it, and the processes and techniques that now form part of the basics of geology have been thoroughly detailed, leaving no room for doubt
Includes Bibliography and index
Keywords: Geology; Earth sciences; Petrology; Mineralogy; Structural geology; Stratigraphy